Breaking the Cycle of Gridlock. Issue 1 (14th February 2018) - Hale, Thomas; Held, David
Abstract: There is a growing gap between the need for effective global governance and the ability of intergovernmental institutions to provide it. In Gridlock: Why Multilateralism Is Failing when We Need It Most, published in 2013, we argued that self‐reinforcing interdependence, rooted in the extraordinary success of the post‐war multilateral order, has created a range of 'second‐order problems' that are threatening to undermine our ability to engage in further global cooperation. As we show in this article, gridlock is itself reinforcing and structurally embedded in global politics. The corrosive effect of unmanaged globalization on domestic politics is provoking anti‐global backlashes that further erode the capacity of intergovernmental institutions to provide solutions to global problems. It is possible, however, to detect a number of significant counter‐trends and exceptions to global governance dysfunction. We set out seven pathways 'through' and 'beyond' gridlock, explain their significance, and provide examples of how these pathways can effect positive change. While none of these pathways alone offer a silver bullet, they all highlight possible ways of moving towards a more resilient, adaptive, and innovative global governance arrangement. Abstract : Although it has been shown that most change is incremental, transformative change beyond gridlock does happen. Major leaps forward in the institutional structures of nations and the world order often follow major wars and calamities. But political wisdom requires that we learn to make significant and strategic changes before tragedies unfold, and not just with hindsight.